KOMBINASI METODE PENJEMURAN DAN PENGERINGAN TUMPUKAN UNTUK MEMPERBAIKI MUTU BIJI KAKAO KERING - Tya Lestari; Leopold Oscar Nelwan; Emmy Darmawati; Samsudin Samsudin; Eko Heri Purwanto (The University of Lampung, 2020)
Deficiencies in the drying and stacking methods of cocoa beans can be minimized by using a combination of both to improve quality. The purpose of this study was to obtain physicochemical and organoleptic quality information of dried cocoa beans produced by a combination of drying and stack drying. The treatments analyzed were drying 3, 8 and 16 hours followed by mechanical drying using an air flow of 0.05 m/s and 0.2 m/s at a temperature of 55 °C. As a control is only mechanical drying with two flow rates, up to a water content <6%. Measurement data were analyzed using descriptive statistics and mean values. The best combination of drying and mechanical drying is found in 8 hours of drying with an air flow velocity of 0.05 m/s and 0.2 m/s. The combination of sun and mechanical drying has no effect on physical parameters namely water content and pH, chemical parameters namely total fat and fermentation index. The best color of cocoa beans is produced from a combination of 16 hours of drying with an air flow rate of 0.05 m/s. The lowest free fatty acid levels come from full mechanical drying with an air flow velocity of 0.05 m/s and 3 hours drying in the air flow velocity of 0.2 m/s. The combination of the best treatment based on the special requirements of SNI 2008 about the quality of defective seeds and organoleptic test results were produced by 8 hours drying air velocity of 0.05 m/s and 0.2 m/s. Included in the IB quality class and has the aroma, texture and color most preferred by panelists. Keywords: air flow, bed dryer, cacao quality, dried cacao, sundrying